Calculation of Fermi level location and point defect ensemble in CdTe single crystal and thin films - Kosyak, V.V.; Opanasyuk, A.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
With the use of expressions obtained from the “first principles”, the ensemble
of point defects was calculated, and the location of a Fermi level in undoped cadmium
telluride single crystals and thin films depending on physico-technological conditions of
their fabrication and annealing is determined. The model in use accounts the most
complete spectrum of defects in chalcogenide, including defects in the cadmium and
tellurium sublattices, and the existence of an antistructural defect on the cadmium
sublattice. Calculations of the concentration of neutral and charged defects are realized
for two extreme cases – full equilibrium and quenching. The comparison of the obtained
results with the data of modeling provided with the use of a quasichemical formalism for
a number of models most used presently is carried out. It is shown that all models
describe well the results of Hall measurements of the concentration of free carriers in
single crystals in the range of high cadmium pressure, but give essentially different
results in the range of high tellurium pressure. Dominant defects in single crystals at high
cadmium pressure and annealing temperatures are twice charged tellurium vacancies or
interstitial cadmium atoms, which is in agreement with experimental results, as just such
defects can provide the dependence of the concentration of free carriers on cadmium
pressure as n ~ P¹/³Cd . A type of defects which are dominant in a tellurium-enriched
material is determined by the chosen model. This allows us to make conclusions about
the validity of the considered models and to specify the thermodynamic parameters of the
defect creation processes in a material.
The offered model can be used for modeling the ensemble of point defects in any А₂В₆
compounds. Thus, the problem of the choice of models adequate to experimental data is
reduced to the determination of the creation energy for uncharged defects and the depth
of energy levels of charged defects.